2013
DOI: 10.1111/adb.12028
|View full text |Cite
|
Sign up to set email alerts
|

GDNF is a novel ethanol‐responsive gene in the VTA: implications for the development and persistence of excessive drinking

Abstract: Glial cell line-derived neurotrophic factor (GDNF) is a potent inhibitor of ethanol consumption and relapse (Carnicella et al., 2008; Carnicella and Ron, 2009; Carnicella et al., 2009c; Barak et al., 2011a), and GDNF heterozygous knockout mice display increased reward sensitivity to ethanol, and consume more ethanol after a period of abstinence, than their wild-type littermates (Carnicella et al., 2009b). Here, we tested whether ethanol alters GDNF expression in the ventral tegmental area (VTA; GDNF’s site of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 37 publications
2
61
1
Order By: Relevance
“…In Long-Evans rats, typically about 20% of the animals fail to reach this criterion. However, if the research question refers to the general population, such as the effects of certain manipulations on escalation in ethanol drinking (see Ahmadiantehrani, Barak, & Ron, 2013) or individual differences, then no selection of high drinkers should be conducted to avoid the loss of valuable data and misrepresentation of the population. Unfortunately, information as to whether and according to what criteria rats have been excluded from the study is not readily available in most IA2BC studies, and non-standard exclusion criteria might account for the variability in ethanol intake and BEC levels (see Table 1 and below).…”
Section: Intermittent Access To 20% Alcohol In 2-bottle Choicementioning
confidence: 99%
See 1 more Smart Citation
“…In Long-Evans rats, typically about 20% of the animals fail to reach this criterion. However, if the research question refers to the general population, such as the effects of certain manipulations on escalation in ethanol drinking (see Ahmadiantehrani, Barak, & Ron, 2013) or individual differences, then no selection of high drinkers should be conducted to avoid the loss of valuable data and misrepresentation of the population. Unfortunately, information as to whether and according to what criteria rats have been excluded from the study is not readily available in most IA2BC studies, and non-standard exclusion criteria might account for the variability in ethanol intake and BEC levels (see Table 1 and below).…”
Section: Intermittent Access To 20% Alcohol In 2-bottle Choicementioning
confidence: 99%
“…However, within 3–4 weeks of training they gradually escalate to consume considerably higher amounts, namely, 5–6 g/kg/24 h, with ~50% ethanol preference (Carnicella, Amamoto, et al, 2009; Carnicella et al, 2008; Simms et al, 2008). This gradual escalation from moderate to excessive ethanol drinking can potentially model the transition from moderate “social”-like drinking to excessive alcohol drinking in humans (e.g., Ahmadiantehrani et al, 2013; Barak et al, submitted). Interestingly, Carnicella, Amamoto, and colleagues (2009) showed that about one-third of the total ethanol amount consumed throughout the 24-h session is consumed within the first 30 min, generating a BEC of > 80 mg%, which meets the criteria of the National Institute on Alcohol Abuse and Alcoholism (NIAAA) for binge drinking in humans (National Institute on Alcohol Abuse and Alcoholism, 2004).…”
Section: Intermittent Access To 20% Alcohol In 2-bottle Choicementioning
confidence: 99%
“…We further reported that the consequence of this alteration of the endogenous levels of BDNF is a breakdown of the protective corticostriatal BDNF pathway (Logrip et al, 2009b). In addition, we recently reported that endogenous VTA GDNF expression is substantially reduced in rats experiencing withdrawal from long-term 2BC excessive alcohol drinking (Ahmadiantehrani et al, 2013). It should be noted however, that although the responsiveness of the GDNF gene to alcohol is altered after chronic excessive drinking, the pathway itself appears to be unperturbed.…”
Section: Dysregulation Of Protective Genesmentioning
confidence: 97%
“…Interestingly, we found that the GDNF heterozygote knockout (HET) mice consumed more alcohol than their WT littermates after a period of abstinence and exhibit increased CPP for alcohol (Carnicella, Ahmadiantehrani, Janak, & Ron, 2009), suggesting an important role for the endogenous growth factor in the regulation of alcohol intake. To this end, we recently demonstrated that both the mRNA and protein levels of GDNF are increased in the VTA of rats after the first week of the 20% 2BC alcohol-drinking procedure (Ahmadiantehrani, Barak, & Ron, 2013). Furthermore, shRNA-mediated knockdown of GDNF in the VTA led to an accelerated escalation of alcohol intake (Ahmadiantehrani et al, 2013) and, notably, the level of VTA GDNF expression was negatively correlated with the amount of alcohol consumed (Ahmadiantehrani et al, 2013).…”
Section: Protective Signaling Pathwaysmentioning
confidence: 98%
See 1 more Smart Citation